An organo-NHC catalyzed domino addition approach for the selective synthesis of 5-butynylisoxazoles and subsequent Sonogashira coupling1. Issue 93 (11th October 2015) - Kankala, Shravankumar; Jonnalagadda, Sreekantha B.; Vasam, Chandra Sekhar
<x xml:space="preserve">Abstract</x> An organo-NHC catalysed domino addition approach for the selective synthesis of 5-butynylisoxazoles and the subsequent Sonogashira cross-coupling for the selective synthesis of corresponding internal alkynes is described.